Clinical case of peripheral facial palsy as first and single COVID-19 symptom in an immunized patient - Savytska, Iryna B. (Psychiatry, Neurology and Medical Psychology, 2021)
SARS-CoV-2 virus affects the central as well as the peripheral nervous system. Peripheral facial palsy is possible as the first and single COVID-19 symptom. The author presents own clinical observation of a 58-year-old patient with peripheral facial palsy. It is known that the patient completed the vaccination 8 weeks ago and also had direct contact with the patient SARS-CoV-2 (the patient’s son). Facial nerve palsy was the first and only symptom of coronavirus infection. In the blood there was a moderate lymphocytopenia, increased interleukin-6, C-reactive protein, seromukoids. MRI of the brain and CT of the temporal bones did not reveal focal and diffuse pathology. After treatment, there was a complete recovery on the ninth day of treatment. Treatment included antiviral drugs, vitamins, steroids, kinesiotaping of facial muscles. The author substantiates necessity and demonstrates the results of treatment with endothelioprotective therapy (combination of L-arginine and L-carnitine) , which is aimed at elimination of systemic inflammation, oxidative stress caused by SARS-CoV-2 virus. Conclusions. General practitioner need to be alert when examining patients, including those who have been vaccinated and those who have direct contact with patients with coronavirus infection. Pathogenesis of peripheral facial palsy in COVID-19 multidirectional: neuroinvasive and neurotropic effect of the virus on the nerve, hypercoagulation, ischemia of the peripheral nerve on the background of systemic inflammatory reaction, oxidative stress. Timely detection, careful monitoring and adequate treatment of pathology are necessary to prevent complications (persistent facial contractures, synkinesis). Further in-depth studies are needed on a larger sample of patients to identify the incidence of peripheral facial nerve palsy in COVID-19 and the possibility of a link to vaccination.